A construção da argumentação em charges políticas: a (co)ocorrência da polifonia e da modalização discursiva - Nascimento, Hugo Fernando da Silva (2021)
This study discourse about the (co)occurrence of two semantic-argumentative phenomena, the enunciative polyphony and the discursive modalization, on political cartoon texts. There was observed that the argumentative phenomena co-occurrence – especially in the cartoon genre – is yet a not well explored subject in studies on the area of Argumentation. Thus it is relevant the execution of an investigation that clarify the way multiple polyphonic or argumentative phenomena can work together to construct the argumentation in the cartoon genre. Assuming this idea, we have established as the central purpose of this study analyze how the phenomenon of polyphony works together with the phenomenon of discursive modalization in order to construct the argumentation in the cartoon genre. The basic theoretical fundamentals that guide this investigation were the studies of Discursive Genres, by Bakhtin (2003), the Theory of the Argumentation in Language, by Ducrot (1988) and the studies of Discursive Modalization, by Nascimento e Silva (2012). The nature of this investigation is descriptive, quali-quantitative and interpretative and it is associated with the linguistic area of Argumentative Semantics. On account to make our corpus, we collected and cataloged an amount of 118 cartoons, of which we analyzed twenty (20). The collected cartoons observed as delimited criterion the 2018 brazilian political elections and their outcomes. Finally, we concluded by means of our analyzes that the usage of the polyphony, in its multiple facets, associated with the discursive modalization function as semantic implement which allows the cartoonist-speaker to construct argumentatively the meaning of the cartoon text, conducting the reader (interlocutor) to specific conclusions sometimes favorable sometimes not to a specific social situation, political figure or a polemic declaration introduced in a cartoon.